Uma análise da aprendizagem de produtos notáveis com o auxílio do programa Aplusix - Rodrigues, Salete (2008)
In this work, we investigate the students' performance of 8 ° and 9 ° years of the basic teaching in the study of notable products with the help of the program of computer Aplusix. He is inserted in the sub-project Expressions, equations and inequations inquiry, teaching and learning , what has like objective characterizes the teaching and Learning on expressions, equations and inequations making possible to develop you investigate in the cognitive, educational plans and curricular of the Group of Inquiry of Algebraic Education (GPEA) of the Program of Postgraduate Studies of the PUC/SP. This work is taken into account the basses resulted from the evaluations SAEB and SARESP and search to include new technologies in the teaching of Mathematics like strategy to win the difficulties of teachers and students. For that, we put the next question of inquiry: Will the program Aplusix be able to contribute to the coordination of registers of representation semiotics regarding the notable products? In what? Which the perceived evolutions? In our analyses we base ourselves on the Theory of the Registers of Representation Semiotics of Duval (2003), through activities that try to favor the learning, making use of conversions between registers of representation and treatment in the same register. The inquiry is qualitative in a diagnostic study with the help of new technologies ruled in the methodology of the Educational Engineering. Three students of a public school of São Paulo participated of ten sessions of 60 minutes each, developing the activities individually. Before the results presented in the protocols, comparing the activities daily pay-test and powders-tests, we note that there was evolution conceptual and significant advancements as for the performance of these students in the conversions between the registers figural, algebraic and numerically and the treatment in the numerical and algebraic registers; we think that that is made a list to the reciprocal actions of the program Aplusix and to the mediation of the investigator that, together, such advancements made possible